PENERAPAN MULTIMEDIA DALAM PEMBELAJARAN YANG EFEKTIF - Nugroho Adi Suryandaru (Journal of Social Studies Arts and Humanities (JSSAH), 2022)
The purpose of this study is to analyze the use ofmultimedia in learning. The research method is meta-analysis. The research beginsby formulating the problem, then proceed by collecting existing research data through Google Scholar search. From the research obtained in theform of 7 relevant scientific journals. Research results from researchers were analyzed by quantitative comparison methods. Based on the resultsof the analysis, the use of multimedia in learning can improve student learning outcomes from the lowest 0.1% to the highest1.2%.